ISOLATION AND ANALYSIS OF BACTERIAL DNA TO DETECT ANTIMICROBIAL RESISTANCE GENES IN WOUND INFECTIONS (Journal of Medical & Health Sciences Review, 2025)
Wound infections are a significant cause of hospital admissions and prolonged treatment, with increasing concern over antimicrobial-resistant bacteria complicating therapy. Rapid identification of bacterial pathogens and their antimicrobial resistance (AMR) profiles is crucial for effective clinical management and infection control. This study aimed to isolate and characterize bacterial pathogens from wound infections, assess their antimicrobial susceptibility patterns, and detect key AMR genes using molecular methods, with detailed quantitative analysis.A total of 150 wound samples were collected over six months from patients aged 18–80 years. Bacterial isolates were identified using standard culture and biochemical methods. Antimicrobial susceptibility was determined by the Kirby-Bauer disk diffusion method following CLSI guidelines. Genomic DNA was extracted using a commercial kit, and PCR was used to detect mecA, bla_TEM, bla_CTX-M, vanA, and tetA genes. Quantitative PCR analysis included ΔCt measurements. Statistical analysis was performed using SPSS v25.0. Of 150 samples, 132 (88%) were culture-positive, yielding 145 bacterial isolates. The predominant pathogens were Staphylococcus aureus (n = 55, 37.9%), Pseudomonas aeruginosa (n = 30, 20.7%), Escherichia coli (n = 25, 17.2%), Klebsiella pneumoniae (n = 20, 13.8%), and Enterococcus spp. (n = 15, 10.3%). Mixed infections were seen in 13 samples (8.7%). Among S. aureus isolates, 28 (50.9%) were methicillin-resistant (MRSA). P. aeruginosa showed ceftazidime and ciprofloxacin resistance in 60% and 50% of cases, respectively. E. coli exhibited 72% resistance to cefotaxime and 48% to gentamicin, while K. pneumoniae had a 75% cefotaxime resistance rate. Vancomycin resistance was seen in 33.3% of Enterococcus isolates. AMR genes were detected in 82 (56.6%) isolates: mecA (96.4% of MRSA), bla_TEM (60% of E. coli, 60% of K. pneumoniae), bla_CTX-M (48% of E. coli, 50% of K. pneumoniae), vanA (80% of vancomycin-resistant Enterococcus), and tetA (36.4% of S. aureus, 40% of E. coli). Multiple AMR genes were found in 40 isolates (27.6%), with bla_TEM + bla_CTX-M most common in Enterobacteriaceae, and mecA + tetA in S. aureus. Multidrug-resistant isolates had significantly lower mean ΔCt values (3.5 ± 0.6) than single-gene carriers (5.1 ± 0.8, p < 0.01), indicating higher gene abundance. Among the 40 multidrug-resistant isolates, 10 (25%) carried three or more AMR genes, mostly from hospital-acquired infections. This study reveals a high prevalence of multidrug-resistant bacteria and AMR genes in wound infections, with significant clinical and infection control implications. Incorporating molecular diagnostics with routine antimicrobial susceptibility testing is critical to optimize treatment, improve outcomes, and curb the spread of resistance. Regular surveillance and tailored antimicrobial stewardship programs are urgently needed in healthcare settings.